Analyse lexico-sémantique de quelques proverbes de la région de M'sila Patrimoine linguistique et transmission - ATAMNIA Halima; BENYAHIA Fatima Zohra (My University, 2025)
Abstract This thesis focuses on the lexico-semantic analysis of a corpus of popular proverbs from the M’Sila region (Algeria). The study explores how the use of dialectal vocabulary, figurative structures (such as metaphor and antithesis), and concise syntactic forms express the social, moral, and cultural representations specific to the local community. The findings show that these proverbs, rooted in oral tradition, play a fundamental role in transmitting norms, regulating behaviors, and preserving regional linguistic identity
Keywords: Keywords Proverbs; M’Sila; Lexicon; Semantics; Dialect; Culture; Orality.